1976
DOI: 10.1104/pp.58.3.398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Stress on Proline Synthesis from Radioactive Precursors

Abstract: Barley (ffordeum vulgare L. var. Prior) leaves converted more '4C-glutamic acid to free proline when water-stressed than when turgid; neither decreased protein synthesis nor isotope trapping by the enlarged free proline pools found in wilted tissue seemed to account for the result. This apparent stimulation of proline biosynthesis in wilted leaves was not observed when radioactive ornithine or P5C (A1-pyrroline-5-carboxylate, an intermediate following glutamate in proline synthesis) were used as proline precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(69 citation statements)
references
References 14 publications
(19 reference statements)
5
61
0
1
Order By: Relevance
“…This is contradictory to the fact that plants under stress continue to synthesize Pro and build up the Pro pool. To explain this paradox, it has been assumed that the P5CS enzyme may undergo a conformational change and lose its feedback regulation property (Boggess et al, 1976a(Boggess et al, , 1976b. We reasoned that if the feedback regulation of the wild-type P5CS is completely lost during stress, then expression of the mutant P5CS, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is contradictory to the fact that plants under stress continue to synthesize Pro and build up the Pro pool. To explain this paradox, it has been assumed that the P5CS enzyme may undergo a conformational change and lose its feedback regulation property (Boggess et al, 1976a(Boggess et al, , 1976b. We reasoned that if the feedback regulation of the wild-type P5CS is completely lost during stress, then expression of the mutant P5CS, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier experiments suggested that Pro accumulation in plants under stress may involve the loss of feedback regulation due to a conformational change in the P5CS protein (Boggess et al, 1976a(Boggess et al, , 1976b. In bacteria, Pro biosynthesis has been shown to be regulated by the end product inhibition of ␥-GK activity (Smith et al, 1984).…”
mentioning
confidence: 99%
“…Experimental procedures were as previously described (3). Briefly, second leaves of 2-week-old barley plants (Hordeum vulgare cv Prior) were excised and allowed to take up radioactive precursor (L-U-_4C-arginine, 50 mCi/mol, obtained from Amersham/Searle and purified by elution from Dowex 50 in the ammonium form) in 4 ,1l aqueous solution.…”
Section: Methodsmentioning
confidence: 99%
“…Glutamic acid and arginine are likely precursors for water stress-induced proline synthesis, as either may be converted to P5C (Al-pyrroline-5-carboxylic acid) which is the immediate precursor of proline. While glutamate is clearly involved in proline synthesis during water stress (1,3,6), the contribution of arginine has not been evaluated. Although leaf tissues typically contain little free arginine, the inexplicably low protein-arginine content of wilted Bermuda grass leaves (1) suggests that in at least some cases, arginine might contribute significantly to the build up of free proline that occurs during water stress.…”
mentioning
confidence: 99%
“…High intracellular proline concentrations may protect against water stress, perhaps by an osmolar effect [l&19]. Proline accumulation probably results from an increased rate of synthesis, though transport may be important in some cases [20]. Studies on proline transport have been reported for algae, plant tissues and organelles [21-251. cultured embryos [30] and cells [29,3 1,321.…”
Section: Introductionmentioning
confidence: 99%